Unilateral optic neuritis following intravenous metronidazole: a case report - Kaleem Basharat; Muhammad Abd Ur Rehman; Nada Saeed Amr Elharabi; Waleed Awad Salem (Toxicology Communications, 2024)
Optic neuritis is an autoimmune condition where demyelination of the optic nerve leads to visual impairment. It is typically associated with autoimmune disorders but can also be triggered by certain drugs known for causing axonal demyelination and nerve fiber degradation. Metronidazole, a common antibiotic, has been identified as one such drug. We describe the acute onset of optic neuritis after a single intravenous dose of metronidazole. Initially presenting with symptoms suggestive of acute gastroenteritis, her condition rapidly progressed to severe visual loss in her right eye following metronidazole administration. She was treated with intravenous steroids and showed good recovery in a follow-up visit. Optic neuritis is an uncommon adverse reaction associated with metronidazole therapy. While the precise cause is under debate, various studies suggest that neuronal damage could be due to free radicals, thiamine analogues, oxidative stress, or the inhibition of protein synthesis. The management of optic neuritis, regardless of the cause, typically involves high-dose corticosteroids.